Silicon application enhances wheat defence against Sitobion avenae F. by regulating plant physiological-biochemical responses - Qi, Xiuxiu; Xue, Xia; Wang, Zhonghua; Li, Shaojian; Zhang, Zelong; Han, Yanlai; Wang, Yi; Jiang, Ying (Basic and applied ecology, 2024)
Sitobion avenae F. is a highly prevalent and devastating pest in wheat crops, leading to significant yield losses. Silicon (Si) has been widely recognized as an effective inducer of plant resistance against aphids. Nevertheless, the underlying mechanisms governing the physiological and biochemical responses of plants induced by Si defense against S. avenae F. remain incompletely understood. In this study, we conducted experiments by treating wheat leaves with varying concentrations of Tetraethyl orthosilicate (TEOS) spray under aphid infestation. We meticulously observed and recorded the life cycle of S. avenae F. and measured the content of plant hormones, secondary metabolites, and the activity of defense enzymes in wheat leaves. Furthermore, we utilized structural equation modeling to discern the causal correlation between aphid performance and the physiological-biochemical responses of wheat under TEOS sprays. Our findings revealed that a concentration of 3 mmol/L TEOS significantly shortened the net reproductive rate, intrinsic rate finite rate of increase, and mean generation time of S. avenae F., while simultaneously prolonging the population doubling time. Additionally, the content of lignin, total phenolics, flavonoids, alkaloids, tannin, jasmonic acid (JA), and salicylic acid (SA) in wheat leaves exhibited a substantial increase. Furthermore, the activity of phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), catalase, and lipoxygenase in wheat leaves was significantly enhanced. Our results suggest that TEOS spray reduced the survival and population growth of S. avenae F. while enhancing the defense response of wheat against aphids by activating the activity of PAL and PPO in wheat, and increasing the content of total phenolic and JA. This work provides valuable insights for the development of appropriate Si fertilizers for effective pest management and offers robust theoretical support for wheat aphid control through agricultural fertilization strategies.